Bi-component weather-resistant adhesive for photovoltaic back plate as well as preparation method and application of bi-component weather-resistant adhesive

Through the dual -component dual -component mixing technology of dual -component adhesives, combined with nano oxides and polymer dispersers, the problem of poor weather resistance and low peeling strength of existing solar photovoltaic backplane adhesives, realized more High weather resistance and peeling strength, and no solvents, have environmental protection advantages.

CN119371925APending Publication Date: 2025-01-28HOHAI UNIV

Patent Information

Application Number
CN202411492782.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The comprehensive performance of existing solar photovoltaic backplane adhesives is insufficient, have poor weather resistance, low peel strength, and the use of solvents leads to environmental pollution and safety hazards.

Method used

The dual -compatible adhesives are used to mix through the polyester resin and modified epoxy resin to increase the cross -linking density, and add nano oxides and polymer dispersers to improve adhesion performance and weather resistance.

Benefits of technology

It significantly improves the weather resistance of the back panel and the interstitial peeling strength, shorten the maturity time, enhances the performance of the backplane glue, extends the outdoor service life of the photovoltaic backplane, and does not need to use solvents, environmentally friendly green.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371925A_ABST
    Figure CN119371925A_ABST
Patent Text Reader

Abstract

The invention discloses a two-component weather-resistant adhesive for a photovoltaic backboard as well as a preparation method and application of the two-component weather-resistant adhesive, and belongs to the technical field of adhesives. The adhesive comprises the following raw materials in parts by weight: a component A: 100 parts of polyester resin, 3-5 parts of a curing agent, 0.5-3 parts of a plasticizer, 0.2-2 parts of a light stabilizer, 0.05-1 part of an antioxidant and 1-2 parts of an anti-hydrolysis agent; the component B comprises the following components in parts by weight: 10-30 parts of modified epoxy resin, 2-10 parts of nano oxide and 0.2-2 parts of a polymeric dispersant. According to the invention, through blending of the component A and the component B, the crosslinking density is improved, the curing time is shortened, the prepared backboard has excellent weather resistance, aging resistance and relatively strong interlayer peeling strength, the use performance of the backboard glue is effectively enhanced, and the outdoor service life of the photovoltaic backboard is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a two-component weather-resistant photovoltaic backboard adhesive and a preparation method and application thereof, belonging to the technical field of adhesives. Background Art

[0002] Epoxy resin is a common adhesive material with advantages such as easy molding, strong adhesion, and good thermal stability. However, its density will continue to increase during the cross-linking process, resulting in increased internal stress, which in turn increases the brittleness of the material and deteriorates its high temperature resistance, which limits its application in many cutting-edge fields. Graphene has excellent mechanical, thermal and electrical properties. As a reinforcing material for modified epoxy resin adhesives, it has attracted widespread attention in nanomaterials.

[0003] Adhesives used in the solar backplane industry are usually two-component solvent-based polyurethane adhesives. This type of adhesive has stable performance. Since a large amount of solvent is used in the compounding process, solvent residue will be generated in the compounding process. The use of solvents has a strong odor when used, and is prone to fire and explosion hazards when used. The use of solvents causes environmental pollution, safety and health hazards. Because it contains solvents, its use, storage and transportation safety risks are high, it is easy to hydrolyze and has poor weather resistance, and its comprehensive performance needs to be further improved.

[0004] Patent CN 104403602 A discloses a solar back panel adhesive and its preparation method, belonging to the field of adhesive technology. The solar back panel adhesive includes the following raw materials: ethylene vinyl acetate copolymer emulsion, polyurethane emulsion, modified epoxy resin, polyvinyl alcohol, turpentine, talcum powder, ethylenediaminetetraacetic acid, magnesium stearate, isopropyl alcohol, and water. The adhesive formed by the components of the invention is relatively soft and has good water vapor barrier performance, but the peel strength is average, and the hydrolysis resistance and weather resistance are far from enough.

[0005] Patent CN 107129764 A discloses a method for preparing an adhesive for a solar cell back panel. The adhesive of the invention has good aging resistance and hydrolysis resistance. After the double 85 test and UV aging treatment, the interlayer adhesion remains above the national standard. However, it is still insufficient to meet the weather resistance requirements on the market, and there are problems of unstable reaction and high equipment cost.

[0006] The backplane is the material that encapsulates the back of the solar cell, and plays a role in protecting and supporting the cell. As a photovoltaic encapsulation material that is directly in contact with the external environment over a large area, the backplane must have excellent aging resistance, hydrolysis resistance, water vapor barrier resistance, etc. Since the backplane adhesive is a key part of the composite backplane, the weather resistance of the adhesive for the solar backplane is particularly important, which is also the performance requirement for producing high-quality backplanes. Summary of the invention

[0007] The present invention provides a two-component weather-resistant adhesive for photovoltaic backplanes, which can solve the problems of insufficient comprehensive performance and poor weather resistance of existing solar photovoltaic backplane adhesives. The adhesive improves the overall cross-linking density through the blending of two components. The prepared backplane has excellent weather resistance and strong interlayer peeling strength, and the aging time is short, which effectively enhances the use performance of the backplane adhesive and improves the outdoor service life of the photovoltaic backplane.

[0008] At the same time, the present invention provides a method for preparing a two-component weather-resistant photovoltaic backplane adhesive, which effectively improves the weather resistance of the polyester backplane adhesive, improves the peel strength, and shortens the aging time.

[0009] At the same time, the present invention provides an application of a two-component weather-resistant photovoltaic backboard adhesive in a solar photovoltaic backboard.

[0010] In order to solve the above technical problems, the technical solution adopted by the present invention is:

[0011] A two-component weather-resistant adhesive for photovoltaic back panels comprises the following raw materials by weight: component A: 100 parts of polyester resin, 3-5 parts of curing agent, 0.5-3 parts of plasticizer, 0.2-2 parts of light stabilizer, 0.05-1 parts of antioxidant, and 1-2 parts of anti-hydrolysis agent; component B: 10-30 parts of modified epoxy resin, 2-10 parts of nano oxide, and 0.2-2 parts of polymer dispersant.

[0012] The preparation method of the modified epoxy resin is as follows: weigh a certain amount of epoxy resin, weigh 7.5-8.5% of graphene by mass, 1-2% of ZnAlCO3-layered double hydroxide material LDH by mass and 30-35% of low molecular weight polyamide resin by mass according to the amount of epoxy resin, mix them evenly, put them into a planetary mixer and stir for at least 20 minutes, after mixing evenly, heat them to 60-65°C on a heating platform, and remove bubbles in vacuum for at least 30 minutes to obtain the modified epoxy resin.

[0013] The molecular weight of low molecular weight polyamide resin is 600-1100, the amine value is 220±20mgKOH / g, the viscosity is 18000mPa.s at 40℃, and the specific gravity is 1.01g / cm at 25℃ 3 , flash point>252℃, active hydrogen equivalent is 195g / Eq, appearance is brown transparent viscous liquid.

[0014] Preferably, the epoxy resin is a composite epoxy resin, which is composited by bisphenol A epoxy resin and bisphenol S epoxy resin, and has a viscosity of 4000-6500 mPa.s.

[0015] Preferably, the nano-oxide is a mixture of one or more nano-titanium dioxide, tin dioxide, molybdenum dioxide, and zinc dioxide with an average particle size of less than 100 nm.

[0016] Preferably, the curing agent is an isocyanate curing agent, selected from one or a mixture of at least two of toluene diisocyanate, diphenylmethane diisocyanate, isophorone diisocyanate, 1,6-hexamethylene diisocyanate and hexamethylene diisocyanate.

[0017] Preferably, the plasticizer is selected from one of dibutyl phthalate DBP, dioctyl phthalate DOP, tricresyl phosphate, triphenyl phosphate or dioctyl sebacate, or a mixture of at least two thereof.

[0018] Preferably, the antioxidant is a hindered amine or a hindered phenol; the antioxidant is selected from any one of antioxidant 1010, antioxidant 1076, antioxidant 1790 or antioxidant BHT, or a mixture of at least two thereof.

[0019] Preferably, the light stabilizer is selected from phenyl salicylate, p-tert-butylphenyl salicylate, 4-[[(methylphenylamine)methylene]amine]benzoic acid acetic acid, 2-cyano-3,3'-ethyl diphenylacrylate, 2,2'-dihydroxy-4-methoxybenzophenone, 2,2',4,4'-tetrahydroxybenzophenone, 2-(2-yl-3',5'-di-tert-butyl)benzotriazole, (2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, 2-(2H-benzotriazol-2-yl)-4-tert-butyl-6-sec-butylphenol or a mixture of at least two thereof.

[0020] Preferably, the anti-hydrolysis agent is selected from at least one of a carbodiimide anti-hydrolysis agent and a polycarbodiimide anti-hydrolysis agent.

[0021] The two-component weather-resistant adhesive for photovoltaic back panels of the present invention has a peeling strength of 8.75-12.59 N / cm after aging, a peeling strength of 6.81-10.82 N / cm after PCT 30h, and a water absorption rate of 0.24-0.75%.

[0022] A method for preparing a two-component weather-resistant photovoltaic backsheet adhesive of the present invention comprises the following steps:

[0023] S01, preparing component B: first, adding a polymer dispersant to the nano-oxide and the modified epoxy resin, dispersing them using a high-speed disperser at a speed of 1000-5000 rpm for 10-60 min to prepare a mixture slurry, i.e., component B;

[0024] S02, prepare component A: weigh 100 parts of polyester resin in a clean crucible according to the proportion, start the stirrer, increase the frequency to 3-5 Hz, weigh and add plasticizer, antioxidant, anti-hydrolysis agent, curing agent and light stabilizer in sequence, and the mixed solution is transparent, which is component A.

[0025] S03, then weigh and mix the component B and component A solutions in proportion, place them on a 95-100°C experimental heating work platform, start the stirrer, increase the frequency to 3-5 Hz, stir for 5-8 minutes, and obtain a mixed glue solution;

[0026] S04, filtering the mixed adhesive solution with a 300-400 mesh filter, ultrasonically degassing until there are no bubbles, and standing at room temperature for 1-2 hours to obtain a two-component weather-resistant photovoltaic backplane adhesive.

[0027] The invention discloses an application of a two-component weather-resistant photovoltaic backsheet adhesive in a solar photovoltaic backsheet. The method of using the two-component weather-resistant photovoltaic backsheet adhesive in a solar photovoltaic backsheet is as follows: when used in combination, the amount of adhesive applied is 15-20 g / m 2 , dry film thickness 12-15μm, composite temperature 100-140℃, applied pressure 8-15kg / cm 2 ; After compounding, ripen at 65-70℃*20-38h.

[0028] Preferably, the polyester resin in the present invention is a base resin, liquid, non-hot melt adhesive, solid content 40-60%, acid value less than 1, hydroxyl value 17±3, 400-600mPa.s. It has a clear and transparent appearance, is a solvent-soluble, linear, thermoplastic polymer polyester, has good leveling, good flexibility, high toughness and high weather resistance, and has good adhesion to PET, PVF / PVDF. It is selected from any one of 50085 or 50087 of Changxing Chemical Industry Co., Ltd. or a mixture of the two.

[0029] Preferably, the epoxy resin in the present invention is bisphenol A type epoxy resin and bisphenol S type epoxy resin, and the obtained A and S type modified epoxy resins have a viscosity of 4000-6500 mPa.s.

[0030] Preferably, the polymer dispersant is one or more mixtures of Disperbyk103, Disperbyk106, Disperbyk107 and Disperbyk110 produced by BYK Chemical Company of Germany.

[0031] The present invention has found through research that adding a plasticizer component can improve the impact toughness and elongation at break of a polymer, reduce the molding temperature of the polymer, and increase the flexibility and bonding strength of the adhesive film.

[0032] The antioxidant of the present invention can inhibit the oxidation process of the backplane adhesive, eliminate the chemical bond breakage of the organic molecules under the action of heat, light or oxygen, generate active free radicals, prevent the chain reaction from proceeding, and further delay the aging process of the backplane.

[0033] The anti-hydrolysis agent of the invention can undergo a cross-linking reaction with a carboxyl-containing resin system to improve water resistance, chemical resistance and wear resistance, and can also enhance adhesion to a substrate.

[0034] The two-component weather-resistant photovoltaic backsheet adhesive of the present invention is easy to use, safe, environmentally friendly and non-toxic, and solves the problems of the existing solvent-based photovoltaic backsheet adhesive being easy to hydrolyze under high humidity and having low peel strength.

[0035] The adhesive prepared by the present invention can be used for the production of solar photovoltaic back panels. The obtained product has been tested and found that under the double 85 temperature for 2000 hours, the adhesive layer has no hydrolysis and stratification, no shrinkage, and no yellowing.

[0036] The beneficial effects achieved by the present invention are:

[0037] (1) Modified epoxy resin has the advantages of good mechanical properties, small curing shrinkage, good thermal stability, strong adhesion, and chemical corrosion resistance. By blending with polyester resin, it can effectively improve the weather resistance of polyester backplane adhesives, increase peel strength, and shorten the aging time.

[0038] (2) Nano dioxide material is added to the main resin. Nano dioxide has excellent water-blocking properties and can effectively prevent hydrolysis between membrane structures. The polymer dispersant used in combination has better dispersing properties, making the entire system more evenly dispersed and reacting more fully, which is beneficial to improving the weather resistance of the adhesive and enhancing the bonding properties of the backplane adhesive.

[0039] (3) The present invention provides a polyester adhesive composition specially designed for solar back panel composite, which does not require the addition of solvents, is environmentally friendly and green, has excellent weather resistance, high interlayer peeling strength, short aging time, and the peeling strength after aging is also higher than the level of traditional adhesives, thereby improving the life of the solar photovoltaic module back panel.

[0040] (4) The adhesive prepared by the present invention can be used in the production of solar photovoltaic back panels. The obtained product has been tested and found that under PCT of 24 h, the adhesive layer does not undergo hydrolysis and delamination, shrinkage, or yellowing. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 It is a comprehensive schematic diagram of the initial peel strength of the adhesive for the back sheet of the solar photovoltaic module of the present invention and the peel strength after PCT 24 h aging;

[0042] Figure 2 It is a schematic diagram of the water absorption rate of the back sheet of the solar photovoltaic module of the present invention. DETAILED DESCRIPTION

[0043] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments. The following embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention.

[0044] Example 1

[0045] A two-component weather-resistant adhesive for photovoltaic back panels comprises the following raw materials, measured by weight: component A: 100 parts of polyester resin, 4.5 parts of curing agent, 0.8 parts of plasticizer, 1 part of light stabilizer, 0.1 parts of antioxidant, and 1 part of anti-hydrolysis agent; component B: 10 parts of modified epoxy resin, 5 parts of nano-oxide, and 0.5 parts of polymer dispersant.

[0046] A preparation method of a two-component weather-resistant photovoltaic backsheet adhesive comprises the following steps: weighing a certain amount of epoxy resin (the epoxy resin is a composite epoxy resin, which is a composite of bisphenol A epoxy resin and bisphenol S epoxy resin, and has a viscosity of 5000 mPa.s), weighing 7.5% by mass of graphene, 1% of ZnAlCO3-layered double hydroxide material (LDH) and 30% by mass of low molecular weight polyamide resin according to the amount of epoxy resin, mixing them evenly, and placing them in a planetary mixer and stirring for 20 minutes. After mixing evenly, heating them to 60°C on a heating platform, and vacuuming and removing bubbles for 30 minutes to obtain a modified epoxy resin.

[0047] Then add 0.5 parts of polymer dispersant Disperbyk103 to 5 parts of nano titanium dioxide and 10 parts of modified epoxy resin, and disperse them with a high-speed disperser at a speed of 2000 rpm for 30 minutes to make a mixture slurry, i.e. component B. According to the proportion, weigh 100 parts of 50085 polyester solution in a clean crucible, slowly start the stirrer, increase the frequency to 3 Hz, weigh 0.8 parts of tricresyl phosphate, 0.1 parts of antioxidant 1076, 1 part of carbodiimide, 4.5 parts of isophorone diisocyanate curing agent, and 1 part of phenyl salicylate, and the mixed solution is transparent, i.e. component A.

[0048] Then, evenly mix the above-mentioned A and B components, place them on a 100°C experimental heating work platform, start the stirrer, increase the frequency to 3 Hz, stir for 8 minutes to obtain a mixed adhesive solution, and then filter the obtained adhesive solution with a 300-mesh filter, ultrasonically degas until there are no bubbles, and let it stand at room temperature for 1.5 hours to obtain a two-component weather-resistant photovoltaic backplane adhesive.

[0049] A two-component weather-resistant photovoltaic backsheet adhesive is used in a solar photovoltaic backsheet. The method of use is as follows: after mixing components A and B according to their respective proportions, the components are coated on the surface of the PET film using a coating rod, and the amount of adhesive applied is controlled at 18g / m 2 After drying at 120℃ for 2min, the PVDF film and the PET coated with glue were laminated together using a laminating machine, and then pressed and flattened using an electric press with a pressure of 10kg / cm 2 ; Dry film thickness 13μm, curing at 70℃*38h after compounding.

[0050] The comprehensive evaluation of the initial peel strength of the prepared back sheet after aging was 8.94 N / cm.

[0051] Example 2

[0052] A two-component weather-resistant adhesive for photovoltaic backsheets, comprising, by weight: component A: 100 parts of polyester solution 50087, 4 parts of isophorone diisocyanate curing agent, 1 part of tricresyl phosphate, 0.2 parts of p-tert-butylphenyl salicylate, 0.05 parts of antioxidant 1076, and 1 part of polycarbodiimide; component B: 20 ​​parts of modified epoxy resin (the epoxy resin is a composite epoxy resin, which is composited by bisphenol A epoxy resin and bisphenol S epoxy resin, and the viscosity of the composite epoxy resin is 4000mPa.s), 7 parts of nano molybdenum dioxide, and 0.6 parts of Disperbyk106.

[0053] A preparation method of a two-component weather-resistant photovoltaic backsheet adhesive comprises the following steps: weighing a certain amount of epoxy resin (the epoxy resin is a composite epoxy resin, which is a composite of bisphenol A epoxy resin and bisphenol S epoxy resin, and has a viscosity of 4000 mPa.s), weighing 8.5% of graphene by mass, 2% of ZnAlCO3-layered double hydroxide material (LDH) and 35% of low molecular weight polyamide resin by mass according to the amount of epoxy resin, mixing them evenly, and putting them into a planetary mixer and stirring for 25 minutes. After mixing evenly, heating them to 65°C on a heating platform, and vacuuming and removing bubbles for 40 minutes to obtain a modified epoxy resin.

[0054] Then add 0.6 parts of polymer dispersant Disperbyk106 to 7 parts of nano molybdenum dioxide and 20 parts of modified epoxy resin, and disperse them with a high-speed disperser at a speed of 1000 rpm for 60 minutes to make a mixed slurry, i.e. component B. According to the proportion, weigh 100 parts of 50087 polyester solution in a clean crucible, slowly start the agitator, increase the frequency to 5 Hz, weigh 1 part of tricresyl phosphate, 0.05 parts of antioxidant 1076, 1 part of polycarbodiimide, 4 parts of isophorone diisocyanate curing agent, and 0.2 parts of tert-butylphenyl salicylate, and the mixed solution is transparent, i.e. component A.

[0055] Then, evenly mix the above-mentioned A and B components, place them on a 95°C experimental heating work platform, start the stirrer, increase the frequency to 5 Hz, stir for 5 minutes to obtain a mixed adhesive solution, and then filter the obtained adhesive solution with a 400-mesh filter, ultrasonically degas until there are no bubbles, and let it stand at room temperature for 1 hour to obtain a two-component weather-resistant photovoltaic backplane adhesive.

[0056] A two-component weather-resistant photovoltaic backsheet adhesive is used in a solar photovoltaic backsheet. The method of use is as follows: after mixing components A and B according to their respective proportions, the adhesive is applied on the surface of a PET film using a coating rod, and the amount of adhesive applied is controlled at 15 g / m 2 After drying at 100℃ for 3min, the PVDF film and the PET coated with glue were laminated together using a laminating machine, and then pressed and flattened using an electric press with a pressure of 8kg / cm 2 ; Dry film thickness 12μm, curing at 70℃*38h after compounding.

[0057] The back sheet prepared in this example had a comprehensive evaluation of initial peel strength of 10.26 N / cm after aging.

[0058] Example 3

[0059] A two-component weather-resistant adhesive for photovoltaic backsheets, comprising, by weight: component A: 100 parts of polyester solution 50085, 3.5 parts of hexamethylene diisocyanate curing agent, 1.5 parts of dioctyl sebacate, 2 parts of 4-[[(methylphenylamine)methylene]amine]benzoic acid acetic acid, 0.2 parts of antioxidant 1076, and 1.5 parts of carbodiimide; component B: 15 parts of modified epoxy resin, 8 parts of nano-tin dioxide, and 1071 parts of Disperbyk.

[0060] A preparation method of a two-component weather-resistant photovoltaic backsheet adhesive comprises the following steps: weighing a certain amount of epoxy resin (the epoxy resin is a composite epoxy resin, which is a composite of bisphenol A epoxy resin and bisphenol S epoxy resin, and has a viscosity of 4500 mPa.s), weighing 8% by mass of graphene, 1.5% of ZnAlCO3-layered double hydroxide material (LDH) and 32% by mass of low molecular weight polyamide resin according to the amount of epoxy resin, mixing them evenly, and placing them in a planetary mixer and stirring for 30 minutes. After mixing evenly, heating them to 60°C on a heating platform, and vacuuming and removing bubbles for 35 minutes to obtain a modified epoxy resin.

[0061] Then add 1 part of polymer dispersant Disperbyk107 to 8 parts of nano-tin dioxide and 15 parts of modified epoxy resin, and disperse them with a high-speed disperser at a speed of 5000 rpm for 10 minutes to prepare a mixture slurry, i.e., component B. According to the proportion, weigh 100 parts of 50087 polyester solution in a clean crucible, slowly start the stirrer, increase the frequency to 4 Hz, weigh 1.5 parts of dioctyl sebacate, 0.2 parts of antioxidant 1076, 1.5 parts of carbodiimide, 3.5 parts of hexamethylene diisocyanate curing agent, and 2 parts of 4-[[(methylphenylamine)methylene]amine]benzoic acid acetic acid, and the mixed solution is transparent, i.e., component A.

[0062] Then, evenly mix the above-mentioned A and B components, place them on a 100°C experimental heating work platform, start the stirrer, increase the frequency to 4 Hz, and stir for 7 minutes to obtain a mixed adhesive solution. Then, filter the obtained adhesive solution with a 300-mesh filter, ultrasonically degas until there are no bubbles, and let it stand at room temperature for 2 hours to obtain a two-component weather-resistant photovoltaic backplane adhesive.

[0063] A two-component weather-resistant photovoltaic backsheet adhesive is used in a solar photovoltaic backsheet. The method of use is as follows: after mixing components A and B according to their respective proportions, the components are coated on the surface of the PET film using a coating rod, and the amount of adhesive applied is controlled at 20g / m 2 After drying at 140℃ for 2min, the PVDF film and the PET coated with glue were laminated together using a laminating machine, and then pressed and flattened using an electric press with a pressure of 15kg / cm 2 ; Dry film thickness 15μm, curing at 65℃*20h after compounding.

[0064] The back sheet prepared in this example has a comprehensive evaluation of initial peel strength of 12.59 N / cm after aging.

[0065] Example 4

[0066] A two-component weather-resistant adhesive for photovoltaic backsheets, comprising, by weight: component A: 100 parts of polyester solution 50085, 3 parts of toluene diisocyanate curing agent, 1.8 parts of dioctyl phthalate (DOP), 0.5 parts of 2-cyano-3,3'-diphenyl acrylate, 0.2 parts of antioxidant 1076, and 1.2 parts of polycarbodiimide; component B: 30 parts of modified epoxy resin (the epoxy resin is a composite epoxy resin, which is composited by bisphenol A epoxy resin and bisphenol S epoxy resin, and the viscosity of the composite epoxy resin is 6500mPa.s), 6 parts of nano zinc dioxide, and 1.2 parts of Disperbyk110. The backsheet prepared by the method of Example 1 has a comprehensive evaluation of initial peel strength of 11.62N / cm after aging.

[0067] Example 5

[0068] A two-component weather-resistant adhesive for photovoltaic backsheets, comprising, by weight: component A: 100 parts of polyester solution 50087, 5 parts of diphenylmethane diisocyanate curing agent, 0.5 parts of dibutyl phthalate, 0.8 parts of 2,2'-dihydroxy-4-methoxybenzophenone, 1 part of antioxidant 1010, 2 parts of carbodiimide; component B: 25 parts of modified epoxy resin, 2 parts of nano molybdenum dioxide, 2 parts of Disperbyk106. The backsheet prepared by the method of Example 1 has a comprehensive evaluation of initial peel strength of 9.48 N / cm after aging.

[0069] Example 6

[0070] A two-component weather-resistant adhesive for photovoltaic backsheets, comprising, by weight: component A: 100 parts of polyester solution 50085, 2 parts of 1,6-hexanediisocyanate, 3 parts of hexamethylene diisocyanate curing agent, 2 parts of tricresyl phosphate, 1 part of triphenyl phosphate, 0.5 parts of 2,2',4,4'-tetrahydroxybenzophenone, 0.5 parts of 2-(2-hydroxy-3',5'-di-tert-butyl)benzotriazole, 0.5 parts of (2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, 0.5 parts of 2-(2H-benzotriazole-2-yl)-4-tert-butyl-6-sec-butylphenol, 0.1 parts of antioxidant 1076, and 0.5 parts of antioxidant BHT. 0.1 part, polycarbodiimide 1.5 parts, carbodiimide 0.5 parts; component B: modified epoxy resin 30 parts, nano-tin dioxide 8 parts, nano-titanium dioxide 2 parts, Disperbyk103 0.1 parts, Disperbyk106 0.1 parts. The back sheet prepared by the method of Example 1 has a comprehensive evaluation of initial peel strength of 8.75 N / cm after aging.

[0071] Comparative Example 1

[0072] This comparative example provides a photovoltaic module backplane adhesive, whose formula and preparation process are the same as those of Example 2, except that the modified epoxy resin in the raw material is removed, that is, the existing epoxy resin is selected in this comparative example, and the epoxy resin is a composite epoxy resin, which is composited by bisphenol A epoxy resin and bisphenol S epoxy resin, and the viscosity of the composite epoxy resin is 4000mPa.s. The prepared backplane has a comprehensive evaluation of initial peel strength of 6.83N / cm after aging at 70℃*72h. In this comparative example, the aging time is 72h to achieve the composite effect.

[0073] Comparative Example 2

[0074] This comparative example provides a photovoltaic module backplane adhesive, the formula and preparation process of which are the same as those of Example 2, except that the nano dioxide in the raw material is removed. The prepared backplane has an initial peel strength of 6.26 N / cm after aging at 70°C*72h. In this comparative example, the aging time is 72h to achieve the composite effect.

[0075] Comparative Example 3

[0076] This comparative example provides a photovoltaic module backplane adhesive, the formula and preparation process of which are the same as those of Example 2, except that the anti-hydrolysis agent in the raw material is removed. The prepared backplane has an initial peel strength of 5.52 N / cm after aging at 70°C*72h. In this comparative example, the aging time is 72h to achieve the composite effect.

[0077] Comparative Example 4

[0078] This comparative example provides a photovoltaic module backplane adhesive, the formula and preparation process of which are the same as those of Example 2, except that the ZnAlCO3-layered double hydroxide material LDH is not added to the modified epoxy resin. The prepared backplane has an initial peel strength of 5.01 N / cm after aging at 70°C*72h. In this comparative example, the aging time is 72h to achieve the composite effect.

[0079] Comparative Example 5

[0080] This comparative example provides a photovoltaic module backplane adhesive, whose formula and preparation process are the same as those of Example 2, except that no low molecular weight polyamide resin is added to the modified epoxy resin. The prepared backplane has an initial peel strength of 5.47 N / cm after aging at 70°C*72h. In this comparative example, the aging time is 72h to achieve the composite effect. In this comparative example, the aging time is 72h to achieve the composite effect.

[0081] Comparative Example 6

[0082] This comparative example provides a photovoltaic module backplane adhesive, the formula and preparation process of which are the same as those of Example 2, except that: 5% by mass of graphene, 2% by mass of ZnAlCO3-layered double hydroxide material LDH and 35% by mass of low molecular weight polyamide resin are added to the modified epoxy resin according to the amount of epoxy resin used. The prepared backplane has a comprehensive evaluation of initial peel strength of 5.74 N / cm after aging at 70°C*72h. In this comparative example, the aging time of 72h is required to achieve the composite effect.

[0083] Comparative Example 7

[0084] This comparative example provides a photovoltaic module backplane adhesive, the formula and preparation process of which are the same as those of Example 2, except that: 8.5% of graphene, 0.5% of ZnAlCO3-layered double hydroxide material LDH and 35% of low molecular weight polyamide resin are added to the modified epoxy resin according to the amount of epoxy resin used. The prepared backplane has a comprehensive evaluation of initial peel strength of 6.03N / cm after aging at 70℃*72h. In this comparative example, the aging time of 72h can achieve the composite effect.

[0085] Comparative Example 8

[0086] This comparative example provides a photovoltaic module backplane adhesive, the formula and preparation process of which are the same as those of Example 2, except that: 8.5% of graphene, 2% of ZnAlCO3-layered double hydroxide material LDH and 40% of low molecular weight polyamide resin are added to the modified epoxy resin according to the amount of epoxy resin used. The prepared backplane has a comprehensive evaluation of initial peel strength of 5.82N / cm after aging at 70℃*72h. In this comparative example, the aging time of 72h is required to achieve the composite effect.

[0087] Comparative Example 9

[0088] This comparative example provides a photovoltaic module backplane adhesive, the formula and preparation components of which are the same as those of Example 2, except that the ultrasonic degassing in the preparation process is replaced by static room temperature degassing, the frequency is increased from 3 Hz to 5 Hz, and the aging condition of 70°C*38h in the backplane composite process is replaced by 45°C*24h. The prepared backplane has a comprehensive evaluation of initial peel strength of 4.24N / cm after aging.

[0089] Standard or specific method of testing

[0090] After composite aging, the initial peel strength, peel strength after aging and after boiling water for 1 hour, and back sheet film peeling of each embodiment and comparative example were tested respectively. The results are shown in Table 1, Table 2, and Table 3:

[0091] Peel strength test: Refer to GB / T 2790-1995 Adhesive 180° Peel Strength Test Method for testing. Cut the sample into strips with a width of 10.00 mm and a length of 200 mm, and test at a peeling speed of 130 mm / min.

[0092] Resistance to moisture and heat aging test: PCT test is a peel strength test after the aged sample is placed in an environment of 121℃ and a pressure of 0.1mPa for 30 hours. The test is carried out under the conditions of a peeling speed of 130mm / min and a sample width of 10mm with reference to the method in the national standard GB / T 2790-1995 "Adhesive 180° Peel Strength Test Method Flexible Material to Rigid Material".

[0093] Water resistance: According to GB / T2791, the specimens were immersed in boiling water for 1 hour, and then the peel strength of the bonded samples was tested on an Instron 4465 universal electronic tensile testing machine at a peel speed of 100 mm / min to test the water absorption rate and peel strength drop ratio.

[0094] Table 1 Peel strength evaluation table

[0095]

[0096] Table 2 Back sheet film appearance evaluation table

[0097]

[0098]

[0099] Table 3 Solar back sheet adhesive performance test results

[0100]

[0101] analyze:

[0102] from Figure 1 , Figure 2 , Table 1, Table 2, Table 3 show that the two-component photovoltaic backsheet adhesive composition of the present invention has very good peel strength and excellent weather resistance. Through the examples and comparative examples, the two-component blending has achieved good results, forming a mesh cross-linked structure, improving the bonding performance of the backsheet adhesive, and greatly improving the peel strength and weather resistance of the composite photovoltaic backsheet.

[0103] The addition of modified epoxy resin, which has similar compatibility with the main polyester resin, effectively improves the weather resistance and peel strength of the polyester backplane adhesive, while shortening the curing time.

[0104] At the same time, through comparative examples, it can be found that the nano dioxide used in the present invention has excellent water-blocking properties, effectively preventing hydrolysis between membrane structures; and the polymer dispersant used in combination has better dispersion properties, thereby making the entire system more evenly dispersed and reacting more fully, which is beneficial to improving the weather resistance of the adhesive and enhancing the bonding properties of the backplane adhesive.

[0105] From the examples, we can see that the appearance of PCT is still good after 24 hours of aging, there is no peeling between the adhesive layers, no shrinkage, and no yellowing, which means that the stability of the backplane is significantly improved.

[0106] It should be understood that in order to streamline the present disclosure and aid in understanding one or more of the various inventive aspects, in the above description of exemplary embodiments of the present invention, various features of the present invention are sometimes grouped together into a single embodiment, figure, or description thereof. However, this disclosed method should not be interpreted as reflecting the intention that the claimed invention requires more features than those expressly recited in each claim. Rather, as reflected in the claims, inventive aspects lie in less than all of the features of the previously disclosed embodiments. Therefore, the claims that follow the detailed description are hereby expressly incorporated into the detailed description, with each claim itself serving as a separate embodiment of the present invention.

[0107] Although the present invention has been described according to a limited number of embodiments, it will be apparent to those skilled in the art, with the benefit of the above description, that other embodiments may be envisioned within the scope of the invention thus described. In addition, it should be noted that the language used in this specification is selected primarily for readability and teaching purposes, rather than for explaining or defining the subject matter of the present invention. Therefore, many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the appended claims. The disclosure of the present invention is illustrative, not restrictive, with respect to the scope of the present invention, which is defined by the appended claims.

[0108] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A two-component weather-resistant photovoltaic backsheet adhesive, characterized in that: The raw materials are as follows, measured by weight: Component A: 100 parts of polyester resin, 3-5 parts of curing agent, 0.5-3 parts of plasticizer, 0.2-2 parts of light stabilizer, 0.05-1 parts of antioxidant, 1-2 parts of anti-hydrolysis agent; Component B: 10-30 parts of modified epoxy resin, 2-10 parts of nano oxide, 0.2-2 parts of polymer dispersant.

2. A two-component weather-resistant photovoltaic backsheet adhesive according to claim 1, characterized in that: The preparation method of the modified epoxy resin is as follows: weigh a certain amount of epoxy resin, weigh 7.5-8.5% of graphene by mass, 1-2% of ZnAlCO3-layered double hydroxide material LDH by mass and 30-35% of low molecular weight polyamide resin by mass according to the amount of epoxy resin, mix them evenly, put them into a planetary mixer and stir for at least 20 minutes, after mixing evenly, heat them to 60-65°C on a heating platform, and remove bubbles in vacuum for at least 30 minutes to obtain the modified epoxy resin.

3. A two-component weather-resistant photovoltaic backsheet adhesive according to claim 2, characterized in that: The molecular weight of low molecular weight polyamide resin is 600-1100, the amine value is 220±20mgKOH / g, the viscosity is 18000mPa.s at 40℃, and the specific gravity is 1.01g / cm at 25℃ 3 , flash point>252℃, active hydrogen equivalent is 195g / Eq, appearance is brown transparent viscous liquid.

4. A two-component weather-resistant photovoltaic backsheet adhesive according to claim 2, characterized in that: The epoxy resin is a composite epoxy resin, which is composited by bisphenol A epoxy resin and bisphenol S epoxy resin. The viscosity of the composite epoxy resin is 4000-6500 mPa.s.

5. The two-component weather-resistant photovoltaic backsheet adhesive according to claim 1, characterized in that: The nano oxide is a mixture of one or more nano titanium dioxide, tin dioxide, molybdenum dioxide and zinc dioxide with an average particle size below 100 nm.

6. The two-component weather-resistant photovoltaic backsheet adhesive according to claim 1, characterized in that: The polymer dispersant is a mixture of one or more of Disperbyk103, Disperbyk106, Disperbyk107 and Disperbyk110.

7. The two-component weather-resistant photovoltaic backsheet adhesive according to claim 1, characterized in that: The curing agent is an isocyanate curing agent, selected from one or a mixture of at least two of toluene diisocyanate, diphenylmethane diisocyanate, isophorone diisocyanate, 1,6-hexamethylene diisocyanate and hexamethylene diisocyanate; The plasticizer is selected from one of dibutyl phthalate DBP, dioctyl phthalate DOP, tricresyl phosphate, triphenyl phosphate or dioctyl sebacate, or a mixture of at least two thereof; The antioxidant is a hindered amine or a hindered phenol; the antioxidant is selected from any one of antioxidant 1010, antioxidant 1076, antioxidant 1790 or antioxidant BHT, or a mixture of at least two thereof; The light stabilizer is selected from one or a mixture of at least two of phenyl salicylate, p-tert-butylphenyl salicylate, 4-[[(methylphenylamine)methylene]amine]benzoic acid acetic acid, 2-cyano-3,3'-diphenylacrylate, 2,2'-dihydroxy-4-methoxybenzophenone, 2,2',4,4'-tetrahydroxybenzophenone, 2-(2-yl-3',5'-di-tert-butyl)benzotriazole, (2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, and 2-(2H-benzotriazol-2-yl)-4-tert-butyl-6-sec-butylphenol; The anti-hydrolysis agent is selected from at least one of a carbodiimide anti-hydrolysis agent and a polycarbodiimide anti-hydrolysis agent.

8. The two-component weather-resistant photovoltaic backsheet adhesive according to claim 1, characterized in that: The peel strength after aging is 8.75-12.59 N / cm, the peel strength after PCT30h is 6.81-10.82 N / cm, and the water absorption rate is 0.24-0.75%.

9. A method for preparing a two-component weather-resistant photovoltaic backsheet adhesive according to any one of claims 1 to 8, characterized in that: The following steps are involved: S01, preparing component B: first, adding a polymer dispersant to the nano-oxide and the modified epoxy resin, dispersing them using a high-speed disperser at a speed of 1000-5000 rpm for 10-60 min to prepare a mixture slurry, i.e., component B; S02, prepare component A: weigh 100 parts of polyester resin in a clean crucible according to the proportion, start the stirrer, increase the frequency to 3-5 Hz, weigh and add plasticizer, antioxidant, anti-hydrolysis agent, curing agent and light stabilizer in sequence, and the mixed solution is transparent, which is component A. S03, then weigh and mix the component B and component A solutions in proportion, place them on a 95-100°C experimental heating work platform, start the stirrer, increase the frequency to 3-5 Hz, stir for 5-8 minutes, and obtain a mixed glue solution; S04, filtering the mixed adhesive solution with a 300-400 mesh filter, ultrasonically degassing until there are no bubbles, and standing at room temperature for 1-2 hours to obtain a two-component weather-resistant photovoltaic backplane adhesive.

10. Use of a two-component weather-resistant photovoltaic backsheet adhesive according to any one of claims 1 to 8 in a solar photovoltaic backsheet, characterized in that: The method of using the two-component weather-resistant photovoltaic backsheet adhesive in the solar photovoltaic backsheet is: when used in combination, the amount of adhesive applied is 15-20g / m 2 , dry film thickness 12-15μm, composite temperature 100-140℃, applied pressure 8-15kg / cm 2 ; After compounding, ripen at 65-70℃*20-38h.

Citation Information

Patent Citations

  • Solar backboard glue and preparation method thereof

    CN104403602A

  • Method for preparing adhesive for solar cell backplane

    CN107129764A

Cited By

  • Double-doped modified self-repairing and self-early-warning protective coating and preparation method thereof

    CN119570333A